The Effect of Catalytic Activity of Catalyst (Carrier) Nature in the Synthesis of Vinyl Acetate - Fayzullayev Normurot; Buronov Firdavsiy (International Journal on Human-Computing Studies, 2021)
The article examines the effect of γ-Аl2О3, high-silicon zeolite (HSZ), bentonite, expanded clay, the nature of bentonites, their porous structure, methods of preparation and modes on the activity of the catalyst consisting of palladium, copper and potassium acetate for the vapour phase synthesis of ethylene-vinyl acetate. IR spectra of the synthesized samples were recorded in the reflection mode in the range 400–4000 cm–1 using a Nexus Nicolet Fourier transform IR spectrometer (Thermo Scientific). Thermal studies (TG/DTG-DTA) were carried out on an STA-1500H thermal balance. The specific surface area was determined by low-temperature argon adsorption on a Crystallux-4000M gas chromatograph. The size and radius of the pores were determined using mercury porometry directly on the amount of mercury compressed in them in a mercury porometric device that allows the measurement of the size of the pores. Vinyl acetate synthesis in a pilot device on a catalyst containing 0,4%Рd+4%Cu+7%CH3COOK/HSZ for 2000 hours at a temperature of 165 ℃, a pressure of 0.1 MPa, a vapour-gas mixture at a volumetric rate of 2000 h-1 and the amount of oxygen in the mixture with ethylene Performed when 7 vol.%. During 2000 hours of operation, the catalyst activity was 95-97% selectivity at 370-350 g of vinyl acetate/l. cat. hours.